Detrended fluctuation analysis of EEG patterns associated with real and imaginary arm movements - Pavlov, A.N.; Runnova, A.E.; Maksimenko, V.A.; Pavlova, O.N.; Grishina, D.S.; Hramov, A.E. (Physica A, 2018)
Based on the detrended fluctuation analysis (DFA), we address the problem of recognizing the electrical activity of the brain associated with movements of the right arm and the imagination of this procedure. In experiments with untrained volunteers, we show the possibility to distinguish between the related EEG patterns. We also demonstrate significant distinctions in the scaling features between background records and EEG signals associated with mental intentions that can be transformed to control commands for brain–computer interfaces. This effect is observed in many EEG channels, although individual features of subjects provided various distributions of brain areas with the most prominent differences. •Real and imaginary arm movements are recognized with correlation analysis of EEG.•Mental intentions related to arm movements are detected in the most of EEG- channels.•DFA can be used as data processing algorithm in brain–computer interfaces.